2019
DOI: 10.1021/acs.jpcc.9b01044
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Intramolecular Proton-Transfer Process of Crystalline 6-Cyano-2-(2′-hydroxyphenyl)imidazo[1,2a]pyridine, as Revealed by Femtosecond Pump–Probe Microspectroscopy

Abstract: We have investigated the excited-state dynamics of 6-cyano-2-(2′-hydroxyphenyl)­imidazo­[1,]­pyridine (6-CN HPIP) in tetrahydrofuran (THF) solution and crystalline phases by means of femtosecond transient absorption spectroscopy. In the THF solution, the excited-state intramolecular proton transfer (ESIPT) of the hydrogen-bonded enol form (E form) occurred with a time constant of 0.6 ps, followed by the formation of the excited state of a twisted keto form. On the other hand, in the crystalline phase, heteroex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Furthermore, in TDDFT calculations (Table S2 of the Supporting Information), the corresponding fluorescence of both PD and HP forms showed similar values (PD: λmaxfl =414–418 nm and HP: λmaxfl =414–418 nm). These results suggested that the remarkable fluorescence dependence on various solvents was caused due to a simple polarity dependence, not but excited‐state intramolecular proton transfer . To understand the quantitative photophysical properties of the 15Nap‐X compounds, a Lippert–Mataga plot (Figure ) was drawn by using the Stokes shift Δ ν and the solvent parameter Δ f , which was estimated with Equation , in which ϵ and n are the dielectric constant and refractive index of the individual solvents, respectively. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in TDDFT calculations (Table S2 of the Supporting Information), the corresponding fluorescence of both PD and HP forms showed similar values (PD: λmaxfl =414–418 nm and HP: λmaxfl =414–418 nm). These results suggested that the remarkable fluorescence dependence on various solvents was caused due to a simple polarity dependence, not but excited‐state intramolecular proton transfer . To understand the quantitative photophysical properties of the 15Nap‐X compounds, a Lippert–Mataga plot (Figure ) was drawn by using the Stokes shift Δ ν and the solvent parameter Δ f , which was estimated with Equation , in which ϵ and n are the dielectric constant and refractive index of the individual solvents, respectively. …”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the remarkable fluorescenced ependence on variouss olvents was caused due to as imple polarity dependence, not but excited-state intramolecular proton transfer. [21] To understand the quantitative photophysical properties of the 15Nap-X compounds, aL ippert-Matagap lot [23] (Figure 3) wasd rawn by using the Stokes shift Dn and the solventp arameter Df, which was estimated with Equation(1), in which e and n are the dielectric constant and refractive index of the individual solvents, respectively. The differencei nd ipole momentb etween the ground and excited states Dm was estimated by using Equation (2):…”
Section: In the Solutionstatementioning
confidence: 99%
“…The AIE discovery has led to the resolution of the conventional problem encountered in ACQ, and thus, AIE has been greatly improved for the development of advanced organic luminescent materials. [8][9][10][11] Since then, great efforts have been devoted for developing AIE materials and various AIE-accompanied mechanisms have been proposed to enhance the luminescence efficiency, such as J-aggregate formation, 12 restricted access to the conical intersection (RACI), 13,14 excimer emission, [15][16][17] and excited-state intramolecular proton transfer (ESIPT). [18][19][20][21] In the recent years, organic luminescent materials based on the coupling of AIE and ESIPT mechanisms have drawn widespread attention in bioimaging due to their high efficiency emission in the solid state and large Stokes' shis.…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of aggregation enhanced emissive (AEE) phenomena in non‐planar molecular structure via supramolecular interactions mediated rigidification of intramolecular rotation produced enhanced emissive solids . On the other hand, excited state intramolecular proton transfer (ESIPT) mechanism lead to strong fluorescence in the solid state from planar π‐conjugated molecules . The photoinduced ESIPT from enol (E * ) to keto (K * ) tautomer, proton migration within an intramolecular hydrogen bonding site, exhibited strong emission with large Stokes shift .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excited state intramolecular proton transfer (ESIPT) mechanism lead to strong fluorescence in the solid state from planar π‐conjugated molecules . The photoinduced ESIPT from enol (E * ) to keto (K * ) tautomer, proton migration within an intramolecular hydrogen bonding site, exhibited strong emission with large Stokes shift . Further, the distinct four‐level laser scheme of enol‐keto photocycle (E−E*−K*−K−E) have been made use for developing laser dyes .…”
Section: Introductionmentioning
confidence: 99%